Carbamazepine mitigates parenteral nutrition–associated liver disease in a novel ambulatory piglet model. Issue 6 (15th February 2022) - Song, Eric; Nagarapu, Aakash; van Nispen, Johan; Armstrong, Austin; Manithody, Chandrashekhara; Murali, Vidul; Voigt, Marcus; Samaddar, Ashish; Hutchinson, Chelsea; Jain, Sonali; Roenker, Jeremy; Krebs, Joseph; et al.
Abstract: Background: Parenteral nutrition (PN) remains a critical therapeutic option in patients who cannot tolerate enteral feeding. However, although lifesaving, PN is associated with significant side effects, including liver injury, the etiology of which is multifactorial. Carbamazepine (CBZ), an antiepileptic medication, is known to modulate hepatic fibrosis and hepatocellular injury in a variety of liver diseases. We hypothesized that CBZ could prevent PN‐associated liver disease (PNALD), which we tested by using our novel ambulatory PN piglet model. Methods: Piglets were fitted with jugular catheters and infusion pumps for PN and randomized to enteral nutrition ( n  = 7), PN ( n  = 6), or PN with parenteral CBZ ( n  = 6) for 2 weeks. Serum and liver tissue were analyzed via light microscopy, quantification of serum liver injury markers, Ki67 and cytokeratin‐7 indexing, and real‐time quantitative polymerase chain reaction. Results: PN‐fed piglets in our model developed manifestations of PNALD—particularly, increased serum bilirubin, gamma‐glutamyltransferase, liver cholestasis, and Ki67 expression compared with that of EN‐fed animals ( P  < 0.03). CBZ therapy in PN‐fed animals led to a significant reduction in these markers of injury ( P  < 0.05). Investigation into the mechanism of these therapeutic effects revealed increased expression of sterol regulatory element‐binding protein 1 (SREBP‐1), peroxisome proliferator‐activated receptor alpha (PPAR‐α), and fatty acid binding protein (FABP) in PN‐fed animals receiving CBZ ( P  < 0.03). Further investigation revealed increased LC3 expression and decreased lysosomal‐associated membrane protein (LAMP1) expression with CBZ ( P  < 0.03). Conclusion: CBZ administration mitigates PNALD severity, suggesting a novel therapeutic strategy targeting PN‐associated side effects, and may present a paradigm change to current treatment options.